DAPATKAH TEKNOLOGI INFORMASI MEMENGARUHI KINERJA PEREKONOMIAN? (SEBUAH KAJIAN SPILLOVER DI PULAU SUMATERA) - aan budhi willyana; Erwin Tanur (Bina Ekonomi, 2024)
Mastery of information technology and improvement of human quality is one of the efforts to increase economic output in a region. This study aims to see the effect of information technology on the performance of economic's achievement in Sumatera with the quality of population as a variable control, as well as the possibility of spatial effects between regions in it. The analysis uses panel data covering 154 districts/cities in Sumatera from 2011-2021. Scatterplot analysis and correlation matrix show a positive and strong correlation between the variables of information technology and HDI on economic performance. The results of the Global Moran and Local Moran tests also show a significant spatial effect in terms of the use of information technology and the GRDP per capita of districts/cities in Sumatera. In addition, hot-spots (high-high clusters), cold-spots (low-low clusters), and spatial outliers are formed and show a persistent pattern in 2011 and 2021. The spatial and nonspatial economic performance modeling also shows that computer use is a vital factor affecting regional performance in Sumatera. The spills-over effect that causes positive spatial interactions also indicates that economic progress in an area will affect economic progress in adjacent areas.